Victory at last ; Greening back Mananga ; Small wonder [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Victims of human rights violations during the Marcos regime who scored victory when a Honolulu court granted them damages; The reforestation of the Mananga mountain in Cebu; Shielu Bharwani's performance on stage becoming popular.
Victory at last (18 min.) -- Greening back Mananga (14 min.) -- Small wonder (13 min.).
Reporter, Luchi Cruz-Valdes.
Keywords: Bharwani, Bhielu; Torture victims -- Philippines; Human rights workers -- Philippines; Mananga Mountain (Cebu)